Neoadjuvant chemotherapy followed by interval debulking surgery for unresectable stage IVB Serous endometrial cancer. Issue 1 (February 2019) - Bogani, Giorgio; Ditto, Antonino; Leone Roberti Maggiore, Umberto; Scaffa, Cono; Mosca, Lavinia; Chiappa, Valentina; Martinelli, Fabio; Lorusso, Domenica; Raspagliesi, Francesco
Objective: To test the safety and effectiveness of neoadjuvant chemotherapy followed by interval debulking surgery in unresectable stage IVB serous endometrial cancer. Methods: Data of consecutive stage IVB serous endometrial cancer are reviewed. Patients undergoing neoadjuvant chemotherapy plus interval debulking surgery were propensity matched with patients undergoing primary surgery followed by adjuvant treatment. Results: Thirty-four patients were diagnosed with a stage IVB endometrial cancer. Fifteen (44.1%) patients had neoadjuvant chemotherapy followed by interval debulking surgery; while 19 (55.8%) patients had primary cytoreduction. Among this latter group, 15 (78.9%) patients were selected, using a propensity-matched algorithm. Results of propensity-matching baseline characteristics of patients included were similar between groups. Patients having neoadjuvant chemotherapy plus interval debulking surgery had shorter length of hospital stay (4 [1.40] vs 6 [2.5] days; p=0.011) compared with patients in the control group. Moreover, patients in the neoadjuvant chemotherapy group experienced a trend toward shorter operative time (127 [62] vs 177.6 [84.5] minutes; p=0.072) and lower transfusion rate than patients in the control group (6.6% vs 33.3%; p=0.067). Cytoreduction rate was similar between groups (p=0.962). No difference in postoperative morbidity was recorded. Median disease-free survival was 12.0 vs 15.3 months in the experimental vs control group (p=0.663; log-rank test). Median overall survival was 16.7 vs 18.0 months in the experimental vs control group (p=0.349; log-rank test). Conclusions: Neoadjuvant chemotherapy might be a valuable treatment modality for patients with unresectable stage IVB serous endometrial cancer. Innovative treatments are warranted in this cluster of patients.